2004
DOI: 10.1111/j.1440-1673.2004.01271.x
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous extraperitoneal haemorrhage: Computed tomography diagnosis and treatment by selective arterial embolization

Abstract: Four cases of extraperitoneal haemorrhage occurring in the setting of anticoagulation or coagulopathy are presented. Treatment of this condition has traditionally consisted of reversal of anticoagulation and supportive therapy. Diagnosis was made on contrast-enhanced computed tomography. The finding of active contrast extravasation was found to be a factor predictive of failure of conservative therapy and, therefore, an indication for angiography and embolization. In all four cases presented in the present pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 26 publications
(36 reference statements)
0
25
0
Order By: Relevance
“…Where possible, bleeding vessels should be embolised 13. Recent studies have shown embolisation to be successful in the treatment of ruptured aneuryms secondary to pancreatitis14 and in post-operative bleeding events 15.…”
Section: Discussionmentioning
confidence: 99%
“…Where possible, bleeding vessels should be embolised 13. Recent studies have shown embolisation to be successful in the treatment of ruptured aneuryms secondary to pancreatitis14 and in post-operative bleeding events 15.…”
Section: Discussionmentioning
confidence: 99%
“…Management of SEH usually involves the correction of coagulopathy, fluid resuscitation, blood transfusion, and other supportive measures. Cases of SEH that are unresponsive to the aforementioned therapies are generally treated with surgery; however, the use of angiography and arterial embolization in the treatment of SEH may provide an efficacious alternative to surgery (2,3,14,15).…”
Section: Introductionmentioning
confidence: 99%
“…Spontaneous extraperitoneal hemorrhage (SEH) is typically associated with trauma or surgery (1)(2)(3). Although rare, SEH without associated trauma may be related to coagulopathies, vascular lesions, or pathology (4 -8).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, hemorrhage, an often serious complication of anticoagulant therapy, is reported in up to 4% of treated patients [1,2]. Treatment for anticoagulant-related hemorrhage is mainly conservative, as it has been thought that the bleed resulted from microangiopathy [3]. However, several studies on the role of angiography for detecting and managing anticoagulant-related hemorrhage have been reported [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment for anticoagulant-related hemorrhage is mainly conservative, as it has been thought that the bleed resulted from microangiopathy [3]. However, several studies on the role of angiography for detecting and managing anticoagulant-related hemorrhage have been reported [3,4]. We present a case of lumbar arterial bleeding, secondary to heparin therapy, diagnosed by angiography and successfully treated with transcatheter embolization.…”
Section: Introductionmentioning
confidence: 99%